Моделювання поширення інфекційних захворювань на основі SIR моделей із запізненням - Черевко, Ігор Михайлович (Інститут прикладних проблем механіки і математики ім. Я. С. Підстригача НАН України, 2023)
The work considers the SIR model, which describes the dynamics of the spread of the infectious disease COVID-19. An applied application has been developed for automating the simulation of such models using the proposed algorithms for finding their approximate solutions.
Keywords: диференціальні рівняння із запізненням, SІR модель, різницева схема, числове моделювання